SOCIAL MEDIA ADDICTION AND DECLINING QANA’AH: ISLAMIC PERSPECTIVE ON SELF-ACCEPTANCE - Adiva Fira Elvandari; Karimulloh, Karimulloh (An Natiq, 2025)
This study aims to examine the role of social media addiction in shaping self-acceptance (qana’ah) among emerging adults from an Islamic perspective. Given that qana’ah reflects a believer's satisfaction with divine decree, understanding factors that undermine this trait is essential, particularly amid growing social media use. The study adopted a qualitative library research method, relying primarily on the Qur’an and hadith as authentic sources, supplemented by relevant books, journals, and scholarly articles to provide contemporary context. The findings suggest that excessive social media use negatively affects self-acceptance among emerging adults, leading to traits such as envy, ingratitude, and diminished contentment with one's condition. This implies that digital behavior may conflict with spiritual ideals in Islam, especially during formative adult years. While the study is limited to a literature-based analysis without empirical testing, it offers valuable insights into how Islamic teachings can inform responses to modern psychological challenges. This study contributes original value by integrating classical Islamic concepts with current behavioral concerns, emphasizing the importance of qana’ah in the digital age